How does Irish Healthcare Expenditure compare internationally? - Maev-Ann Wren; Aoife Fitzpatrick (The Economic and Social Research Institute (ESRI), 2020)
The ESRI research report 'How does Irish Healthcare Expenditure compare internationally?' examines how Irish Healthcare Expenditure (HCE) compares to expenditure in other countries. Using international OECD data for 2017, this study finds that how Irish HCE compares differs depending on the expenditure measure used, the service examined and whether the comparison is adjusted for countries' differing approaches to accounting for Social Care Expenditure.
Keywords: 330; Gesundheitswesen; Gesundheitskosten; Irland